2019
DOI: 10.1038/s41467-019-10434-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the energetic driving force for charge generation in organic solar cells

Abstract: Eliminating the excess energetic driving force in organic solar cells leads to a smaller energy loss and higher device performance; hence, it is vital to understand the relation between the interfacial energetics and the photoelectric conversion efficiency. In this study, we systematically investigate 16 combinations of four donor polymers and four acceptors in planar heterojunction. The charge generation efficiency and its electric field dependence correlate with the energy difference between the singlet exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 61 publications
(59 reference statements)
3
110
2
Order By: Relevance
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
“…[4][5][6] As the field of OSCs now moves towards efficient non-fullerene based D-A systems with low voltage losses, surprisingly high external quantum efficiencies (EQEs) are observed even in the absence of a considerable driving force. [7][8][9][10][11] For a number of such D-A systems, it has been shown that the field induced by the presence of electrodes assists the charge generation mechanism. [12,13] This calls for a re-evaluation of charge generation mechanisms in new materials and systems, including the effects of the external field, delocalization, entropy, and driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Compound BThIND‐Cl exhibits somewhat lower energy levels when compared to the ones of BThIND, that may be ascribed to the electron‐withdrawing effect of Cl atom that is increased relative to the H atom, as reported in the literature, [ 59 ] and also be attributed to the dipole moment differences between the carbon–chlorine bond and carbon‐hydrogen bond, with the former being greater. [ 60 ] The HOMO and LUMO energy levels of PM6 are ‐5.47 and −3.61 eV. As shown in the energy level diagram (Figure 3) that the HOMO/LUMO offsets between the BThIND‐Cl/BThIND and PM6 are 0.17/0.35 and 0.13/0.33 eV, respectively.…”
Section: Resultsmentioning
confidence: 97%